Green synthesis of silver nanoparticles from Euphorbia milii plant extract for enhanced antibacterial and enzyme inhibition effects - Bawazeer, Saud (International Journal of Health Sciences, 2024)
Objectives: Silver nanoparticles (AgNPs) are gaining increasing attention in biomedical applications due to their unique properties. Green synthesis methods are environmentally friendly and have demonstrated potential for AgNP production. This study explores the green synthesis of AgNPs using the methanolic extract of Euphorbia milii, a plant known for its medicinal properties. The primary objectives of this research were to synthesize AgNPs using E. milii extract, characterize the nanoparticles (NPs) using various techniques, and evaluate their antibacterial and enzyme inhibitory activities. Methods: E. milii plant extract was utilized for the green synthesis of AgNPs. The characterization of the NPs was performed through ultraviolet-visible spectroscopy (UV-Vis), Fourier-transform infrared spectroscopy, scanning electron microscopy, and energy-dispersive X-ray spectroscopy (EDX). Antibacterial activity was assessed against Staphylococcus aureus, while enzyme inhibitory assays were conducted against urease, α-glucosidase, carbonic anhydrase II, and xanthine oxidase. Results: The synthesized AgNPs exhibited significant antibacterial effects, with a remarkable 20-mm zone of inhibition against S. aureus, surpassing the efficacy of the plant extract alone. Furthermore, the AgNPs demonstrated remarkable enzyme inhibition, achieving impressive percentages of 77.98% against α-glucosidase and 88.54% against carbonic anhydrase II. Half-maximal inhibitory concentration values for enzyme inhibition were highly promising, including 78.09 ± 1.98 μM for α-glucosidase, 0.22 ± 0.10 μM for carbonic anhydrase II, and 7.11 ± 0.55 μM for xanthine oxidase. Conclusion: In this study, AgNPs were successfully synthesized using E. milii extract and characterized using various techniques. The AgNPs exhibited significant antibacterial and enzyme-inhibitory activities, showcasing their potential for biomedical applications.